Peru: Educational level, productivity, personal income and national development 2007 – 2020 - Quispe Llanos, Renán (2023)
The research determined the degree of influence of education on employment, productivity, per capita income, and departmental and national development. Three models were used to explain productivity, income and development respectively, for the historical series from 2007 to 2020. The analysis is deepened in a series of basic traits of people, the most significant of which are: level of studies, age, experience, productivity, quality of employment, and departmental stratum according to standard of living. In response to the objective of the research, the role and impact of education on each of the dependent variables at the national level in the period 2007-2020 was verified. To analyze the impact on national development, a modeling was also made to know the result of education in development by department, as well as its positioning in the national context. Based on the results, it was confirmed that education levels generate a higher level of knowledge, and with it, more opportunities to obtain better levels of employment and productivity, and, consequently, better average income per capita, being, therefore, a factor important in the Departmental and National development.